Aplikasi Penghitungan Gross Primary Production dari Data Penginderaan Jauh - Kurniadi, Komang Gede; Bayupati, I Putu Agung; Putra, I Dewa Nyoman Nurweda (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2016)
Calculation of Gross Primary Production that utilize remote sensing data is can be done on commercial remote sensing software by manual method. The commercial remote sensing software does not provides a specific feature that allow the user to do the Gross Primary Production calculation. This research is aimed to to build a remote sensing software that can be specifically used to do the Gross Primary Production calculation for Denpasar area. This software accepts remote sensing data as an input, such as satellite image from Landsat 8 OLI and TIRS and metadata file. The formulas and supporting data that required on the Gross Primary Production calculation are implemented on software in order to make an automatic image processing software. There also some additional feature on this software such as automatic data parsing from metadata file, cropping, masking and zoom that could help user to do the Gross Primary Production calculation. The developed software is able to produce information such as Gross Primary Production  value that depicted by a figure with color segmentation, area of the segments and mean, minimum and maximum value of the Gross Primary Production.
Keywords: aplikasi; penginderaan jauh; Gross Primary Production; Landsat 8; Denpasar